Bedside angiography of distal perfusion catheter for veno-arterial extracorporeal membrane oxygenation. (July 2022) - Shah, Aakash; Arons, Danielle; Pasrija, Chetan; Kon, Zachary N; Ghoreishi, Mehrdad
Background: The aim of this study was to evaluate the ipsilateral lower extremity (ILE) outcomes of patients who underwent bedside angiography via the distal perfusion catheter while on femoral veno-arterial extracorporeal membrane oxygenation (VA ECMO). Methods: This is a retrospective analysis of all patients placed on VA ECMO at a single center from January 2017 to December 2019 who underwent bedside angiography via the distal perfusion catheter. Results: Twenty-four patients underwent bedside angiography via the distal perfusion catheter after being placed on VA ECMO. A vasodilator was directly administered in three patients for suspected spasm. One patient had distal thrombus and underwent thrombectomy and fasciotomy. One patient had a dislodged catheter and underwent thrombectomy, fasciotomy, and replacement of the catheter. One patient had severe ILE ischemia, however was not intervened upon due to critical acuity. Finally, one patient had inadvertent placement in the saphenous vein and had a new catheter placed in the SFA. No patients underwent amputation. Ultimately, 21 patients (87.5%) had no ILE compromise at the end their ECMO course. Survival to decannulation was 66.7% ( n  = 16). Conclusions: Bedside angiography of the distal perfusion catheter is feasible and can be a useful adjunct in informing the need for further intervention to the ILE. Classifications: extracorporeal membrane oxygenation, ischemia